Role of multiaxial stress state in the hydrogen-assisted rolling-contact fatigue in bearings for wind turbines - J. Toribio; M. Lorenzo; D. Vergara (Fracture and Structural Integrity)
Offshore wind turbines often involve important engineering challenges such as the improvement of hydrogen embrittlement resistance of the turbine bearings. These elements frequently suffer the so-called phenomenon of hydrogen-assisted rolling-contact fatigue (HA-RCF) as a consequence of the synergic action of the surrounding harsh environment (the lubricant) supplying hydrogen to the material and the cyclic multiaxial stress state caused by in-service mechanical loading. Thus the complex phenomenon could be classified as hydrogen-assisted rolling-contact multiaxial fatigue (HA-RC-MF). This paper analyses, from the mechanical and the chemical points of view, the so-called ball-on-rod test, widely used to evaluate the hydrogen embrittlement susceptibility of turbine bearings. Both the stress-strain states and the steady-state hydrogen concentration distribution are studied, so that a better elucidation can be obtained of the potential fracture places where the hydrogen could be more harmful and, consequently, where the turbine bearings could fail during their life in service.